Complex frequencies and field distributions of localized surface plasmon modes in graphene-coated subwavelength wires. (April 2016) - Cuevas, Mauro; Riso, Máximo A.; Depine, Ricardo A.
Abstract: In this work we study the modal characteristics of localized surface plasmons in graphene-coated, circular cross-section wires. Localized surface plasmons are represented in terms of cylindrical multipole partial waves characterized by discrete, complex frequencies that depend on the size of the wire and can be dynamically tuned via a gate voltage. We consider both intrinsically nonplasmonic wires and intrinsically plasmonic wires. In the first case the localized surface plasmons are introduced by the graphene coating, whereas in the second case the localized eigenmodes of the graphene coating are expected to hybridize those already existing in the bare wire. We show that the approach presented here, valid for particle sizes where the retardation effects can be significant, is in good agreement with analytical expressions obtained in the limit when particle size is very small compared to the wavelength of the eigenmode and with results indirectly determined from scattering cross-section spectra. Abstract : Highlights: Modal characteristics of localized surface plasmons are studied. Analytical expressions for resonance frequencies and decay rates are provided. Dielectric and metallic graphene coated wires are considered. Results are compared with those obtained from scattering cross-section spectra.